The synthesis and characterization of novel soluble phthalocyanines substituted with 7-octyloxy-3-(4-oxyphenyl)coumarin moieties - (:unkn) unknown (ELSEVIER SCI LTD, 2008)
Novel, soluble, metal-free phthalocyanine and metallo phthalocyanines (M = Zn, Co, Ni and Cu) bearing four 7-octyloxy-3-(4-oxyphenyl)-coumarin substituents at peripheral positions were prepared by cyclotetramerization of 7-octyloxy-3-[p-(3',4'-dicyanophenoxy)phenyl]coumarin. The lactone rings of the zinc metallo phthalocyanine were opened and the released hydroxyl groups hexylated. The new compounds were characterized by elemental analysis, H-1 NMR, C-13 NMR, IR, mass and UV-vis spectral data. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanine; coumarin; perkin coumarin synthesis; lactone ring opening; metallo phthalocyanines; COUMARIN DERIVATIVES; CROWN-ETHERS